La aplicación del cómic para el desarrollo del nivel inferencial de la comprensión lectora en estudiantes de Décimo “A” de EGB de la Unidad Educativa “Gonzanamá”, período 2022-2023 - Uquillas Vega, César Paúl (2023)
The goal of this study is to examine the incidence of comic book Bestiario on tenth grade students in classroom "A" at Gonzanamá school's inferential level of reading comprehension. The pedagogical intervention is presented under qualitative research with an applied research approach to education. The design of the didactic sequence was carried out through the theoretical adaptation of the comic with the performance criteria of the Reading and Literature block of the Ecuadorian National Curriculum of Education, according to the didactics of reading (Cassany et al. 2003), the canonical school inclusion of the comic (Rovira and Ortiz, 2015), the comic (Eisner, 1985; Gubern, 1972 and McCloud 1995), the integrative model of text and image comprehension (Schnotz and Bannert, 2003) and multimodal literacy (Hodge and Kress, 1988). The results show that the implementation of the comic book Bestiario (2018) in the educational context developed the inferential level of reading comprehension, as students interpreted verbal language in order to gain inferential reading comprehension by using visual language and conventional sign language to interpret the implicit content of the work, specifically in establishing the plot, interpreting graphic signs in order to understand the protagonists' emotional and physical states, and the relationship between the events and their social and cultural context.